ASSESSMENT OF EFFECT OF SANDMINING ACTIVITIES ON PHYSICOCHEMICAL PROPERTIES AND METAL CONCENTRATIONS OF SURFACE WATER OF WARRI RIVER, NIGER DELTA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The Warri River in Niger Delta, Nigeria is one River in which indiscriminate and commercial sand mining activities have been taking place in recent times. Thus, this study was carried out to assess the effect of sand mining activities on physicochemical properties and metal concentrations of surface water of the Warri River, Niger Delta, Nigeria. Water samples were collected from six sand mining sites along the Warri River between January and December, 2016. The physicochemical properties and heavy metal concentrations of water samples were determined following the methods of the American Public Health Association. The result showed that electrical conductivity, turbidity, total suspended solids, total solids, salinity, total hardness, biochemical oxygen demand and the heavy metals (Cd, Cr, Cu, Pb, Mn, Ni and Fe) exceeded the World Health Organization (WHO) maximum permissible values. Temperature, pH, total dissolved solids, alkalinity, sulphate, nitrate, chloride, dissolved oxygen, chemical oxygen demand, calcium, magnesium, sodium, potassium and Zn were within their respective WHO maximum permissible values. Health risk assessment indicated no adverse non-carcinogenic risk, whereas there was a potential carcinogenic risk associated with metals in the water while quality index values indicate unsuitability of the water for drinking purposes
Keywords: Sandmining, Warri River, Physicochemical properties, Metals, Water quality index